Anisotropic elasticity and plasticity of an organic crystal - Wang, Jian-Rong; Li, Meiqi; Yu, Qihui; Zhang, Zaiyong; Zhu, Bingqing; Qin, Wenming; Mei, Xuefeng (Chemical communications (Cambridge, England), 2019)
Organic crystals are generally considered to be brittle, inelastic materials, which pose challenges for application in flexible devices. Inspired by α helical proteins for their key structural role in flexible hair, here, we describe the construction of a spring-like hydrogen bonded network through the self-assembly of a-OH/e-OH cyclohexanol derivatives. Two-in-one bending properties were achieved by a crystal engineering strategy of introducing a spring-like backbone in the structure.